PENGARUH SELF EFFICACY, INDEPENDENSI DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGMENT - Hendrawan, Agus; Dirmawan, Muhamad Reza (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
This study aims to determine the effect of Self Efficay, Independence and Time Budget Pressure on Audit Judgment. this research is included in the type of quantitative research using primary data with a survey method in the form of distributing questionnaires to public accounting firms in the South Jakarta area. The sampling technique used was non-probability sampling. This research data testing was processed using SMART-PLS version 4.0 as a data analysis tool. The results of this study indicate that (1) self efficacy has a positive and significant effect on audit judgment, (2) independence has a positive and significant effect on audit judgment, (3) time budget pressure has a positive and significant effect on audit judgment, (4) self efficacy, independence and time budget pressure together have a positive and significant effect on audit judgment.Keywords : Self Efficacy, Independence, Time Budget Pressure, and Audit Judgment